Neighborhood context, genetic influences, and life satisfaction: Evidence from the German twin family panel - Nadia V. Harerimana; Yixuan Liu; Mirko Ruks (PLoS ONE, 2025)
Both genetic influences and neighborhood environments play a role in shaping life satisfaction. However, research examining gene-environment interactions (GxE) in this context remains limited. This study investigates how neighborhood deprivation moderates the effects of genetic influences on life satisfaction. Using data from 760 dizygotic (DZ) twin pairs in the German Twin Family Panel (TwinLife), we apply twin fixed-effect models to estimate GxE effects. Results indicate that a Polygenic index (PGI) for subjective well-being is positively associated with life satisfaction. Notably, this association is strongest among individuals living in moderately deprived neighborhoods, and weaker in both highly deprived and less deprived areas. Thus, there are signs of compensation in less deprived areas and, particularly, diathesis-stress/triggering in highly deprived areas.